Old problems in the face of new challenges (Global Journal of Science Frontier Research, 2023)
Introduction-Humanity is currently facing new challenges in the context of the evolving COVID-19 (SARS-CoV-2) pandemic. The epidemiological situation in connection with COVID-19 causes the greatest tension in society around the world. The situation throughout the world, unfortunately, is getting worse. In this regard, new measures for the prevention of coronovirus infection are actively recommended and are being developed. One of such measures to prevent the spread of the disease, recommended by WHO and Rospotrebnadzor of the Russian Federation, along with the use of masks and gloves, is the use of disinfectants and sanitizers at work places, in transport, educational institutions, and at home. They are liquid (rarely gel) agents that destroy most harmful microorganisms and viruses, as stated by the manufacturer. The composition of most of these products that enter the distribution network includes ethyl or isopropyl alcohol, triclosan, propylene glycol, formic acid, sometimes salicylic acid, all kinds of fragrances and other substances. Moreover, if traditionally, in order to guarantee the effectiveness of an antiseptic, clinical trials are necessarily carried out with the issuance of an opinion on behalf of a certified scientific center, in the case of sanitizers, usually classified as a cosmetic product, manufacturers do not face many difficulties.